Investigation of Possibility of Measuring the Albedo of Earth's Surface in Visible and Near Infrared Bands in Conditions of Aerosol Pollution of Atmosphere Using Unmanned Aerial Vehicles - H. H. Asadov; A. J. Alieva; M. G. Ashrafov (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ)
It is well-known that such processes as agricultural activities, urbanization processes, climatic changes leading to abnormal precipitation, etc. affect the magnitude of the Earth's albedo. At the same time, the results of remote albedo measurement in visible and near infrared bands also depend on the degree of aerosol pollution of the atmosphere. These factors leading to changes in the earth's albedo lead to the need for periodic measurements of regional values of the albedo of the earth's surface. There are a number of problems related to measuring the albedo of the earth, related to the spatial and temporal variability of this indicator. These include the dependence of albedo on the zenith angle of the Sun, the need to create albedo measurement networks in the form of numerous geographically distributed pyranometers, the dependence of satellite albedo measurements on the state of the atmosphere, leading to the need for inter-satellite calibration, or ground-based validation measurements. At the same time, the issue of fully accounting for the effect of atmospheric aerosol on the results of measuring the albedo of the Earth's surface is still open. The article is devoted to the measurement of the Earth's albedo visible and near infrared bands using UAVs in conditions of aerosol pollution of the atmosphere. The model of single scattering of the optical source signal of an atmospheric aerosol was adopted as the basis of the conducted research. The interrelation of such optical indicators as the optical thickness of the aerosol and the albedo of the Earth's surface is analyzed. A criterion for the effectiveness of atmospheric measurements using UAVs is proposed, in which efficiency is defined as the ratio of the total radiation entering the on-board spectroradiometer to the amount of extra-atmospheric radiation from the Sun. By switching from a discrete model to a continuous model created to calculate the proposed efficiency criterion, it is shown that with a synchronous change in the optical thickness of the aerosol and albedo, according to the calculated law, the minimum efficiency of measurements of the albedo of the earth's surface is achieved.